Political Economic Dilemma of Member Countries of the Eurasian Economic Union (UEE) - Putra, Gilang Rizki Aji; Yunus, Nur Rohim; Abdurofiq, Atep (BULETIN ADALAH, 2023)
This article examines the political economy dilemma faced by member countries of the Eurasian Economic Union (UEE), a regional economic bloc consisting of countries in Eurasia. The UEE includes several countries with significant natural resource wealth and broad economic diversity. Focusing on the challenges of economic diversification, this article analyzes UEE's efforts to reduce dependence on the energy sector and develop other economic sectors. This research also explores the internal political dynamics that influence economic decisions in the context of UEE regional integration.